Multimessenger Multi-TeV Dark Matter - Gammaldi, Viviana (Frontiers in Astronomy and Space Sciences, 2019)
We briefly review the general insight into the indirect searches of dark matter. We discuss the primary equation in a three-level multimessenger approach (gamma rays, neutrinos and antiprotons), and we introduce the reader to the main topics and related uncertainties (e.g. dark matter density distribution, cosmic rays, particle physics). As an application of the general concept, we focus on the multi-TeV dark matter candidate among other weak interactive massive particles. We present the state-of-the-art on this sub-field, and we discuss open questions and experimental limitations.